Numerical study of thermal diffusion in a passive autocatalytic recombiner: Possible effects on catalyst temperature and hydrogen distribution. (15th April 2023) - Malakhov, A.A.; Avdeenkov, A.V.; du Toit, M.H.; Duong, Q.H.; Bessarabov, D.G.
Abstract: This paper describes a numerical study of the influence of thermal diffusion (the Soret effect) on the operational behaviour of a passive autocatalytic recombiner (PAR). The study proposes a detailed three-dimensional computational fluid dynamics (CFD) model of hydrogen oxidation along a cylindrical-type PAR catalyst section (RVK-500, RET, Russia) inside a small-scale vertical channel. The CFD model was developed in STAR-CCM+ and uses multi-step chemical kinetics with a conjugated approach (surface and gas-phase included). The catalyst temperature and hydrogen conversion with and without the Soret effect in the model were determined numerically and compared against experimental measurements. The experiments reported here have previously been conducted on the cylindrical-type catalyst section, for 5–7 vol % inlet H2 concentration. Numerical simulations demonstrate that local hydrogen concentration can be increased due to thermal diffusion at the lower side of the stainless-steel frame. Results identified that the catalyst temperature can be underpredicted by 10–20 °C without thermal diffusion included in the model. Highlights: Numerical simulations were performed to analyze the thermal diffusion (Soret effect) in a PAR. CFD model includes a conjugated approach for chemical kinetics of catalytic hydrogen oxidation. Increase of 0.4–0.6 vol % in local hydrogen concentration due to the thermal diffusion was identified numerically. Neglected thermal diffusion in CFD model can cause underprediction in catalyst temperature by 10–20 °C. Results are valuable for PAR validation and relevant safety research.